The importance of co‐stimulation in the orchestration of T helper cell differentiation. Issue 9 (21st April 2015) - Coquet, Jonathan M; Rausch, Lisa; Borst, Jannie
Abstract : Upon their activation, CD4 T cells can differentiate into distinct T helper cell subsets with specialised functions. Different T helper cell subsets produce specific cytokines that mediate beneficial and sometimes detrimental effects, depending on the infection or disease setting. CD4 T‐cell priming relies on signals delivered by the T‐cell antigen receptor, co‐stimulatory receptors and cytokine receptors on the CD4 T‐cell surface. Cytokine receptors are well known to deliver instructive signals that direct T helper cell differentiation. However, it is less appreciated that co‐stimulatory receptors also exert potent modulatory effects on this process. In this review, we outline the contribution of co‐stimulatory and co‐inhibitory receptors to the process of T helper cell differentiation, focusing on those pathways for which the underlying mechanisms are best known. Herein, we depict the physiological context of T‐cell priming and emphasise the impact of cell–cell communication on directing T helper cell differentiation.